Pengaruh Efektivitas Revisi PP No 81 Tahun 1999 Tentang Pengamanan Rokok bagi Kesehatan dengan PP No 19 Tahun 2003 Terhadap Kesehatan Masyarakat - Maria Rosarie Harni Triastuti (Jurnal Administrasi Publik, 2004)
In 1999, the Government published PP No. 81 /1999 on Cigarettes Security for Health which one of section (section 4) address the limitation of nicotine and tar of cigarettes in Indonesia. The set of policy problem were rising when there were pressures to change PP No. 81 /1999 with PP No. 19/2003. The policy change invited some protest from interest parties on public health. The analysis of this essay depict that the PP reflect that the government have no committmen on public health. The formulation process of this PP strongly influenced by cigarettes company and interest parties in cigarettes industry.Kata kunci : perubahan kebijakan, pendekatan supply dan demand, nilai ekonomi, nilai kesehatan